A description of the first instar of Hoperius Planatus fall, 1927 (Coleoptera: Dytiscidae: Colymbetinae: Colymbetini), with phylogenetic implications - Barman, E. H. (2014)
The first instar of Hoperius planatus Fall, 1927 is described and illustrated for the first time with an emphasis on the chaetotaxy of the head capsule, head appendages, legs, last abdominal segment, and urogomphi. Hoperius planatus is characterized by the presence of additional campaniform sensilla (pores) on the frontoclypeus, representing a unique character state within the tribe Colymbetini (Colymbetinae). A phylogenetic analysis based on 42 first-instar characters using the program TNT reinforces the hypothesis of monophyletic origin of the Colymbetini and suggests a placement of Hoperius Fall, 1927 as sister to a clade comprised of Neoscutopterus J. Balfour-Browne, 1943, Meladema Laporte, 1835, and Bunites Spangler, 1972. Members of this clade are uniquely characterized within the Colymbetini by the presence of a large number of additional spiniform sensilla on the urogomphus.